Observations Directly Linking Relativistic Electron Microbursts to Whistler Mode Chorus: Van Allen Probes and FIREBIRD II. Issue 22 (29th November 2017) - Breneman, A. W.; Crew, A.; Sample, J.; Klumpar, D.; Johnson, A.; Agapitov, O.; Shumko, M.; Turner, D. L.; Santolik, O.; Wygant, J. R.; Cattell, C. A.; Thaller, S.; et al.
Abstract: We present observations that provide the strongest evidence yet that discrete whistler mode chorus packets cause relativistic electron microbursts. On 20 January 2016 near 1944 UT the low Earth orbiting CubeSat Focused Investigations of Relativistic Electron Bursts: Intensity, Range, and Dynamics (FIREBIRD II) observed energetic microbursts (near L = 5.6 and MLT = 10.5) from its lower limit of 220 keV, to 1 MeV. In the outer radiation belt and magnetically conjugate, Van Allen Probe A observed rising‐tone, lower band chorus waves with durations and cadences similar to the microbursts. No other waves were observed. This is the first time that chorus and microbursts have been simultaneously observed with a separation smaller than a chorus packet. A majority of the microbursts do not have the energy dispersion expected for trapped electrons bouncing between mirror points. This confirms that the electrons are rapidly (nonlinearly) scattered into the loss cone by a coherent interaction with the large amplitude (up to ∼900 pT) chorus. Comparison of observed time‐averaged microburst flux and estimated total electron drift shell content at L = 5.6 indicate that microbursts may represent a significant source of energetic electron loss in the outer radiation belt. Plain Language Summary: Relativistic microbursts are impulsive (<1 s), energetic (MeV) bursts of electrons precipitated from the magnetosphere into the atmosphere. They may constitute a major source of electron loss that helps bring the outer radiation belt back to quiet time levels following storm time enhancements. One possible cause of microbursts is scattering by a VLF plasma wave called chorus. However, simultaneous measurements of microbursts and chorus are extremely rare and this connection has not previously been directly shown. We provide the strongest evidence yet that chorus causes relativistic microbursts by comparing simultaneous observations from the Van Allen Probes and the Focused Investigations of Relativistic Electron Bursts: Intensity, Range, and Dynamics CubeSat. Results indicate that microbursts may indeed be an important source of energetic electron loss in the outer radiation belt. Key Points: First published conjunction of simultaneous chorus and microbursts with a separation smaller than a chorus packet Observations provide strongest evidence yet that chorus causes microbursts, from subrelativistic (200 keV) to relativistic (1 MeV) energies The scattering is prompt and occurs off equator; it may be a significant source of relativistic electron loss in the outer belt